A Systematic Review: Assessment of the Metabolomic Profile and Anti-Nutritional Factors of Cannabis sativa as a Feed Additive for Ruminants - Tumisho Ntsoane; Ndivho Nemukondeni; Lufuno Ethel Nemadodzi (Metabolites)
Background: Cannabis sativa is a high-value crop that can be cultivated for ruminant’s feed and medicinal purposes. The demand for Cannabis and Cannabis products has increased since the beginning of 21st century. Objectives: The increase in the production cost of high-protein feeds such as lucerne has led to an urgent need to investigate alternative high-protein sources. Methods: Cannabis has been identified as an alternative to lucerne due to its high protein content. Results: However, the cultivation and uses of Cannabis and its by-products in South Africa is limited due to the strict legislation. The metabolites and nutritional value of Cannabis are influenced by growing conditions and soil type. Furthermore, the available literature has shown that Cannabis contains anti-nutritional factors that may affect feed intake or bioavailability and digestibility. Conclusions: Therefore, it is crucial to employ a processing method that can reduce anti-nutritional factors to promote the feed intake and growth rate of sheep. Fermentation, as a processing method, can reduce anti-nutritional factors found in Cannabis, which will make it a palatable alternative feed supplement for ruminants such as Dorper sheep. Overall, this review paper aimed to examine the available literature on the use of Cannabis as an alternative high-protein feed supplement for Dorper sheep in South Africa.